Development of antioxidant bilayer films based on polyethylene, gelatin and fruit peel extracts for food packaging - Abdullah, Nor Adilah (2018)
In this research, utilization of agricultural by-products as a source of natural antioxidant was developed for an active packaging system. In the first objective, four types of by-products namely, jackfruit peels (JPE), mango peels (MPE), pineapple peels (PPE), and papaya peels (YPE) in the form of extracts were incorporated into fish gelatin films to determine their physical and antioxidant properties. Films with three different concentrations of extracts (1, 3 and 5%) were prepared by solution casting method. Increasing concentration of extracts up to 5% produced thicker, colored, good tensile strength and less flexible films. It also showed an improvement in water permeability with less solubility. Although all films have potential to be developed into active packaging, gelatin based film with 5% MPE was more outstanding in availability of phenolic compounds and its antioxidant performances. Therefore, in the second objective, 5% MPE-gelatin based film was developed into bilayer active packaging by casting onto the PE films at 10 μm (PE/G10), 20 μm (PE/G20), 40 μm (PE/G40), and 60 μm (PE/G60). Bilayer films also showed compatibility structure without any separation between the PE and gelatin active layer. Thicker coatings influenced the reduction (p≤0.05) of the total phenolic content (TPC) values. Besides, thicker coating layer had improved the transparency and the antioxidant ability but increased (p≤0.05) the water vapor permeability. Therefore, it can be suggested that bilayer film is suitable for low water activity of food products. In the third objective, PE/G60 was used to determine the effectiveness of the bilayer films on maintaining or controlling the quality of margarine during storage at 4 °C and 25 °C. Results observed that margarine packed in PE/G60 at 4 °C able to inhibit lipid oxidation during 28 days of storage. The bilayer material affects the color changes in margarine with no significant (p>0.05) differences were observed on pH of margarine for both temperatures. This concluded that 5% MPE at 60 μm was suitable to be developed into bilayer films and had the potential as an antioxidant packaging for high lipid product.